Optical properties of cometary particles collected by the COSIMA mass spectrometer on-board Rosetta during the rendezvous phase around comet 67P/Churyumov–Gerasimenko - Y. Langevin; M. Hilchenbach; M. Vincendon; S. Merouane; K. Hornung; N. Ligier; C. Engrand; R. Schulz; J. Kissel; J. Rynö; COSIMA team (United Kingdom, 2022)
40 000 collected cometary particles have been identified on the 21 targets exposed by the COSIMA experiment on-board Rosetta to the environment of comet 67P/Churyumov–Gerasimenko from 2014 August to 2016 September. The images of the targets where obtained by the COSIMA microscope (Cosiscope, 13.95 μm pixel−1) with near grazing incidence, which is optimal for the primary objective (detection of collected particles) but very challenging for photometry. However, more than 300 of the collected particles are larger than 100 μm which makes it possible to derive constraints on the optical properties from the distribution of light levels within the particles. Two types of particles collected by COSIMA (compact particles and cluster particles) have been identified in Langevin et al. The best estimate reflectance factors of compact particles range from 10 per cent to 23 per cent. For cluster particles (>90 per cent of large collected particles), the comparison of the signal profiles with illumination from two opposite directions shows that there is scattering within the particles, with a mean free path in the 20–25 μm range, which requires high porosity. The best estimate reflectance factors of cluster particles range from 3 per cent to 22 per cent. This range of reflectance factors overlaps with that obtained from observations of the cometary nucleus at macroscopic scales by OSIRIS and it is consistent with that measured for interplanetary dust particles collected in the stratosphere of the Earth.